(untitled) - Diaz, James H. (Boca Raton, FL, 2006)
This book is the only full-color resource available for the immediate identification of envenoming species, resultant lesions, clinical outcomes, and recommended treatments. Organized in an easily accessible fashion, the atlas offers general information on poisoning management and antidotes. With bulleted text, tables, figure legends, and diagrams, this atlas provides an immediate reference for use in emergency situations."--BOOK JACKET
Keywords: Poisoning,Poisons,Toxicology,Nhiễm độc,Chất độc,Độc tố học